Tectonic constraints from thin granitoid sheets in H.U. Sverdrupfjella, Western Dronning Maud Land, Antarctica - Roberts, R.J. (James) (University of Pretoria, 2023)
Thesis (PhD (Geology))--University of Pretoria, 2023.